Emotional Intelligence Differences Between Male and Female Adolescents - Atiqul Ilmi El Faisal; Netrawati Netrawati (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
This study aims to determine differences in the level of emotional intelligence in male and female adolescents. This research is a type of comparative descriptive quantitative research. The population used in the study was 1060 students of SMAN 1 Kampar Timur who were enrolled in the 2022/2023 school year with a sample of 290 students who were selected using the proportional random sampling technique. Data collection was carried out using an emotional intelligence questionnaire which was arranged based on aspects of emotional intelligence. Data were processed using descriptive analysis techniques and comparative analysis techniques T-Test. The results showed that: 1) as many as 38.6% of students have moderate emotional intelligence; 2) as many as 37.2% of male adolescents have moderate emotional intelligence of male adolescents; 3) as many as 35.9% of young women have moderate emotional intelligence; 4) there is no difference in emotional intelligence in middle adolescents in terms of gender with the result sig = 0.078 (sig. > 0.05).TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian // TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//